Experienced-based environmental education: Workshop on the value of wild birds to promote positive attitudes and behaviors among the rural school students of La Cataluña, Tacares, Alajuela, Costa Rica (Biocenosis, 2023)
Cataluña is a rural community in Costa Rica, mainly dedicated to local agriculture. Its environmental context has a great biodiversity of wildlife, including birds such as the Keel-billed Toucan, the Lineated woodpecker, and the Scarlet macaw, among others. During the bird nesting season, adult men capture chicks to trade and sell. In addition, children and adults find it normal to kill birds and other animals, as a form of entertainment. As a project of an Environmental Education course at the University of Costa Rica, a workshop was held with fifth graders from La Cataluña School. The objective was to promote positive attitudes and behaviors towards wild birds, through awareness and knowledge. The workshop consisted of an experience-based exercise in which they observed and identified birds that visit the school. In addition, a talk was given on the values and environmental services that wild birds provide to the community. To evaluate the workshop, the children made drawings through which we were able to identify more knowledge and positive attitudes towards wild birds. We believe that these workshops could also influence the environmental attitudes and behaviors of adults.
Keywords: attitude; birds; drawings; environmental education; animal abuse; experience-based workshop